Indonesia's Strategy in Maritime Defense Diplomacy to the State FPDA members (Malaysia, Singapore, Australia, New Zealand, and United Kingdom) - Susilowati, Ida; Maulida, Savira; Hartadi, Najla Aulia (UIN Jakarta, 2024)
Indonesia has long established cooperative and diplomatic relations with the five FPDA member countries. However, this relationship still arouses a sense of mistrust from all parties with the emergence of issues and tensions in diplomatic relations. The presence and establishment of FPDA itself is also one of the reasons to